2014
DOI: 10.1186/1743-422x-11-125
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of irradiation and herpes simplex virus type 1 infection on an immortal gingival cell line

Abstract: BackgroundOral mucosa is frequently exposed to Herpes simplex virus type 1 (HSV-1) infection and irradiation due to dental radiography. During radiotherapy for oral cancer, the surrounding clinically normal tissues are also irradiated. This prompted us to study the effects of HSV-1 infection and irradiation on viability and apoptosis of oral epithelial cells.MethodsImmortal gingival keratinocyte (HMK) cells were infected with HSV-1 at a low multiplicity of infection (MOI) and irradiated with 2 Gy 24 hours post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Both HMK and HaCaT keratinocytes are nontumorigenic, spontaneously immortalized cell lines and do not contain any human papilloma virus DNA (Boukamp et al 1988;Turunen et al 2014). Although the origin of HaCaT cells is skin, this cell line has been widely used in multilayered cell culture models of the oral cavity and infection-related responses of this cell line against periodontal pathogens were demonstrated (Gursoy et al 2010(Gursoy et al , 2016Zeidán-Chuliá et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both HMK and HaCaT keratinocytes are nontumorigenic, spontaneously immortalized cell lines and do not contain any human papilloma virus DNA (Boukamp et al 1988;Turunen et al 2014). Although the origin of HaCaT cells is skin, this cell line has been widely used in multilayered cell culture models of the oral cavity and infection-related responses of this cell line against periodontal pathogens were demonstrated (Gursoy et al 2010(Gursoy et al , 2016Zeidán-Chuliá et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be attributed to their genetic origins; gingival kerationcytes have significantly higher proliferation and migration rates in comparison with skin keratinocytes (Rowat and Squier 1986). Moreover, HaCaT cells have hypotetraploid karyotypes, while HMK cells have total tetraploid karyotypes (Turunen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This observation led us to design an in vitro study to assess the effects of irradiation on HPV16-and HSV-1 co-infected epithelial cells. The results showed that HSV-1 infection may modulate the radiation resistance of HPV16-positive HNSCC cells by increasing cell survival after irradiation, most likely through the escape of apoptosis [19]. Given that oral epithelium is often exposed to radiation during dental radiography, it is relevant to assess the frequency of oral HSV-1 and HPV co-carriage in asymptomatic persons.…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis to explain the lack of dual infections in our study population is that epithelial HSV infection is often lytic and leads to elimination of the infected cell [2]. On the contrary, HPV infection of epithelial cells can be less lytic and immunologically more silent, thereby persisting for longer intervals [19]. The rare dual infections may thus represent either a state of dual infection when HSV infection has not yet led to elimination of the cell, or a rare long-term quiescent HSV infection could take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation